Examining the co-occurrences of human threats within terrestrial protected areas - Martini, Francesco; Kounnamas, Constantinos; Goodale, Eben; Mammides, Christos (Ambio, 2024)
Human threats to biodiversity are prevalent within protected areas (PAs), undermining their effectiveness in halting biodiversity loss. Certain threats tend to co-occur, resulting in amplified cumulative impact through synergistic effects. However, it remains unclear which threats are related the most. We analyzed a dataset of 71 human threats in 18 013 terrestrial PAs of the European Union's Natura 2000 network, using a Joint Species Distribution Modelling approach, to assess the threats' co-occurrence patterns and potential drivers. Overall, threats were more frequently correlated positively than negatively. Threats related to agriculture and urbanization were correlated strongly with most other threats. Approximately 70% of the variance in our model was explained by country-specific factors, indicating the importance of local drivers. Minimizing the negative impact of key threats can likely reduce the impact of related threats. However, more research is needed to understand better the relationships among threats and, importantly, their combined impact on biodiversity.
Keywords: ekosystém; Urbanization; Post-2020 Global Biodiversity Framework; Anthropogenic impact; Natura 2000; lidé; Biodiversity; Joint Species Distribution Modeling; Ecosystem; Humans; Agriculture; Conservation of Natural Resources; Human pressure; biodiverzita; zachování přírodních zdrojů; urbanizace; Biodiversity conservation; zemědělství